Aetiological role of bacteria associated with reactive arthritis in pauciarticular juvenile chronic arthritis. - Sieper, J (1992)
BACKGROUND: The cause of juvenile chronic arthritis (JCA) is unknown. Pauciarticular JCA is the most common subtype and can be subdivided into early (type I) and late onset (type II) forms, the latter clinically resembling reactive arthritis. METHODS: The cellular immune responses to bacteria associated with reactive arthritis in blood and synovial fluid from 39 children with pauciarticular JCA, three children with classical reactive arthritis, and two children with psoriatic arthritis were examined. Specific titres of antibodies to bacteria in serum samples were measured in all patients. RESULTS: A bacteria specific synovial cellular immune response was found in two of three (67%) patients with reactive arthritis and 14 of 28 (50%) patients with pauciarticular JCA type II but only in one of 11 (9%) patients with pauciarticular JCA type I and none in patients with psoriatic arthritis. Six patients responded specifically to Chlamydia trachomatis and 11 to Yersinia enterocolitica. Antigen specific lymphocyte proliferation correlated poorly with the specific antibody response. CONCLUSIONS: These findings suggest that bacteria with associated reactive arthritis may have a causative role in pauciarticular JCA type II but not in JCA type I.